SPEECH DEVELOPMENT OF PRESCHOOL CHILDREN IN THE CONDITIONS OF RUSSIAN-UKRAINIAN BILINGUAL - Onyshchenko, I.V. (Pedagogy of Higher and Secondary Education, 2008)
In article the essence and prominent features of speech development of children in conditions bilingvizm reveals, pedagogical conditions of the organisation of training of children of the Ukrainian language in a preschool educational institution with training Russian are defined.